Detection of mycoplasma gallisepticum by real time PCR using gapA gene - Yasmin, Farhana; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair; Tan, Sheau Wei; Tan, Ching Giap; Islam, R.; Ahmad, K. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Mycoplasma gallisepticum (MG) is responsible for chronic respiratory disease which leads to a lot of economic losses to the poultry industry. Therefore, it is very important to detect this organism early and efficiently. MG can be diagnosed by three ways: isolation identification, serological method and molecular detection method. In this study, a SYBR green real time PCR assay by using gapA gene was developed for the detection of MG. This assay was powerful both from the aspect of specificity and sensitivity as it amplified only MG at early cycle when run together with 20 other avian Mycoplasma species and it can detect a minimum of 26 pg/μl of DNA template.